2011
DOI: 10.1002/cbdv.201000086
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Chemical Composition and the Organoleptic Profile of Virgin Olive Oil from Two Wild and Two Cultivated Tunisian Olea europaea

Abstract: With the aim to select new olive cultivars with superior physical and chemical properties than the cultivar Chemlali Sfax, the present study focused on the comparison of the chemical composition and the sensory profile of the virgin olive oils (VOOs) of two wild olive trees (Oleasters K and M) with those of VOOs obtained from Chemlali Sfax and Neb Jmel olive cultivars, all growing in the coastal region of Tunisia. Despite the variability in the chemical composition (fatty acids, pigments, and phenolic and vola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
32
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 62 publications
8
32
3
Order By: Relevance
“…In comparing the studied varieties, small but significant differences among the samples were shown; indicating a slight varietal effect on fatty acid composition. Furthermore, as the fatty acid composition is an important quality parameter and authenticity indicator of EVOO, these results are in agreement with other studies in which nutritional properties of EVOO have been described [22]. The high content of monounsaturated, low saturated and linoleic fatty acids, which characterize in particular some of the studied samples, the European EVOO and, among them, the Italian EVOO, is of great importance because of their high nutritional value and positive effect on the oxidative stability of oils [23].…”
Section: Resultssupporting
confidence: 92%
“…In comparing the studied varieties, small but significant differences among the samples were shown; indicating a slight varietal effect on fatty acid composition. Furthermore, as the fatty acid composition is an important quality parameter and authenticity indicator of EVOO, these results are in agreement with other studies in which nutritional properties of EVOO have been described [22]. The high content of monounsaturated, low saturated and linoleic fatty acids, which characterize in particular some of the studied samples, the European EVOO and, among them, the Italian EVOO, is of great importance because of their high nutritional value and positive effect on the oxidative stability of oils [23].…”
Section: Resultssupporting
confidence: 92%
“…The description of oleaster and olive cultivars and/or the relationships between them were conducted using several markers as morphological traits (Bartolini et al, 1998;Rotondi et al, 2003;Idrissi & Ouazzani, 2003;Hannachi et al, 2008a,b;Belaj et al, 2011), oil criteria (Baccouri et al, 2011;Dabbou et al, 2011;Krichene et al, 2007;Hannachi et al, 2013) and molecular markers (Belaj et al, 2007;Belaj et al, 2010;Hannachi et al, 2010;Erre et al, 2010;Belaj et al, 2011;Noormohammadi et al, 2014).…”
Section: Olea Europaea Trees Spread In the Mediterraneanmentioning
confidence: 99%
“…However, compositional quality of VOOs from wild origin has been scarcely studied. Some works comparing oil composition between cultivars and wild olives indicate overlapping results between the two groups ( Hannachi et al, 2008 ; Dabbou et al, 2011 ; Boucheffa et al, 2014 ). While it seems that fruit size and oil content (OC) are determinant traits to discriminate between wild and cultivated forms ( Hannachi et al, 2008 ; Belaj et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…While it seems that fruit size and oil content (OC) are determinant traits to discriminate between wild and cultivated forms ( Hannachi et al, 2008 ; Belaj et al, 2011 ). Wild olives yielding high quality oils were suggested to be commercially useful ( Baccouri et al, 2008 ; Dabbou et al, 2011 ), although a possible feral origin of the genotypes reported to have high OC cannot be excluded ( Baccouri et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%